Die Namenskodierung mit den Buchstabenentsprechungen der Tönen in der deutschen Musiktradition. B-A-C-H als Idee, Ideal und Ideologie - Gramatikov, Iliya (Zeitschrift „Germanistik und Skandinavistik“ / Journal for German and Scandinavian Studies, 2024)
Тhe present study examines several compositions representative of the German musical tradition, wherein the basic musical material has been derived through the cryptographic procedure of encoding names with the letter designations of the pitches (i.e. letter notation). Three main thematic lines are highlighted in the research: the possible meanings embedded in the works by means of the applied cryptographic compositional approach; the tradition among German composers of inlaying tone monograms in their works of significance; the application of musical cryptographic procedures as a strategy of artistic legitimation. The starting point of the analysis is the idea of Bach’s personality and music as an enduring ideal that remains relevant – a foundation of a creative ideology that evolves over time.
Keywords: musical cryptography; composers’ monograms; Johann Sebastian Bach; Robert Schumann; Arnold Schönberg